2019
DOI: 10.3390/plants8090338
|View full text |Cite
|
Sign up to set email alerts
|

SWEET Gene Family in Medicago truncatula: Genome-Wide Identification, Expression and Substrate Specificity Analysis

Abstract: SWEET (Sugars Will Eventually be Exported Transporter) proteins mediate the translocation of sugars across cell membranes and play crucial roles in plant growth and development as well as stress responses. In this study, a total of 25 SWEET genes were identified from the Medicago truncatula genome and were divided into four clades based on the phylogenetic analysis. The MtSWEET genes are distributed unevenly on the M. truncatula chromosomes, and eight and 12 MtSWEET genes are segmentally and tandemly duplicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 74 publications
6
30
0
Order By: Relevance
“…In Medicago truncatula [25], cucumber [16], banana [13], Brassica rapa [6], cabbage [17], tomato [19], soybean [23], rubber tree [18], cotton [54], and pear [55], more than half of the SWEET members have six exons and five introns, suggesting that during evolution the molecular features of SWEET genes were highly conserved. Here, the gene structure analysis of ClaSWEET genes indicated that 12 members (about 54.5%) harbored six exons and five introns.…”
Section: Discussionmentioning
confidence: 99%
“…In Medicago truncatula [25], cucumber [16], banana [13], Brassica rapa [6], cabbage [17], tomato [19], soybean [23], rubber tree [18], cotton [54], and pear [55], more than half of the SWEET members have six exons and five introns, suggesting that during evolution the molecular features of SWEET genes were highly conserved. Here, the gene structure analysis of ClaSWEET genes indicated that 12 members (about 54.5%) harbored six exons and five introns.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, two putative auxin efflux carriers, similar to the PIN-like PILS 5 and 7 proteins from Arabidopsis (Sauer and Kleine-Vehn, 2019) were found associated with the primary root response after 5 days in response to Nod-LCOs. For the root growth response to Fung-LCOs at 5 days, we also identified the MtSWEET3c locus that was shown to transport mannose and sucrose and to be expressed in Medicago nodules or roots upon abiotic stress (Hu et al, 2019).…”
Section: Genetic Determinants Underlying Quantitative Variation In Root Responsiveness To Fungand Nod-lcos In Medicago Truncatulamentioning
confidence: 99%
“…It is therefore impossible to speak strictly about the clade division of the SWEET genes for the types of the transferred substrate (see Suppl. Material 1) (Hu B. et al, 2019).…”
Section: Phylogenetics Of the Sweets Isoformsmentioning
confidence: 99%
“…The intron-exon structure of the SWEET genes may also vary notably (Cao et al, 2019). Most of the MtSWEET genes (in M. truncatula) contain 5 introns, excluding the genes MtSWEET4, MtSWEET6, MtSWEET7 and MtSWEET13 which include 4 introns, and MtSWEET2b which contains 16 introns (Hu B. et al, 2019). The structure of the M. truncatula SWEET proteins is also heterogeneous: most contain 7 TMHs, but MtSWEET4 and MtSWEET11 have 6 TMHs, and MtSWEET2b contains 15 TMHs instead of 7 (Hu B. et al, 2019).…”
Section: Phylogenetics Of the Sweets Isoformsmentioning
confidence: 99%